Apolipoprotein A-I Mimetic Peptides: Discordance Between In Vitro and In Vivo Properties—Brief Report. Issue 7 (July 2017) - Ditiatkovski, Michael; Palsson, Jonatan; Chin-Dusting, Jaye; Remaley, Alan T.; Sviridov, Dmitri
Abstract : Objective—: Apolipoprotein A-I (apoA-I) mimetic peptides have antiatherogenic properties of high-density lipoprotein in vitro and have been shown to inhibit atherosclerosis in vivo. It is unclear, however, if each in vitro antiatherogenic property of these peptides translates to a corresponding activity in vivo, and if so, which of these contributes most to reduce atherosclerosis. Approach and Results—: The effect of 7 apoA-I mimetic peptides, which were developed to selectively reproduce a specific component of the antiatherogenic properties of apoA-I, on the development of atherosclerosis was investigated in apolipoprotein E–deficient mice fed a high-fat diet for 4 or 12 weeks. The peptides include those that selectively upregulate cholesterol efflux, or are anti-inflammatory, or have antioxidation properties. All the peptides studied effectively inhibited the in vivo development of atherosclerosis in this model to the same extent. However, none of the peptides had the same selective effect in vivo as they had exhibited in vitro. None of the tested peptides affected plasma lipoprotein profile; capacity of plasma to support cholesterol efflux was increased modestly and similarly for all peptides. Conclusions—: There is a discordance between the selective in vitro and in vivo functional properties of apoA-I mimetic peptides, and the in vivo antiatherosclerotic effect of apoA-I-mimetic peptides is independent of their in vitro functional profile. Comparing the properties of apoA-I mimetic peptides in plasma rather than in the lipid-free state is better for predicting their in vivo effects on atherosclerosis. Abstract : Supplemental Digital Content is available in the text.